Acting out and working through in Chimimanda Ngozi Adichie's Half of a Yellow Sun - Jamal, Malissa; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2015)
Half of a Yellow Sun, written by Chimamanda Ngozi Adichie, is a novel filled with notions of tragedy, strife and survival. This novel recounts the experiences of characters who lived in a country torn apart by a civil war resulting from political upheaval. This study elucidates the trauma concepts of acting out and working through as done by the main characters of this novel. Furthermore, it ascertains why the characters are traumatised, the effects of the trauma and whether they recover from such trauma. There are quite a few concepts related to trauma theory, which is the literary theory used here as it best suits this research study. However, the main focus of this study is the concepts of acting out and working through from Dominick LaCapra. A close reading of Chimamanda Ngozi Adichie's novel in the light of trauma theory provides insight into how to understand the horrors of trauma. People are often ignorant of the horrors of trauma and how it can affect a person, unless they undergo trauma themselves. Furthermore, since trauma theory has been largely linked to the medical rather than the literary field, it is viewed as a contemporary theory, unlike post-colonialism or feminism. Therefore, this study will be beneficial to literary students and people who conduct research in the same field of study.